3D model retrieval scheme based on fuzzy clustering for physical descriptors. Issue 1 (March 2016) - Zou, Kuansheng; Zhang, Zhaojun; Zhang, Jianhua; Liu, Jia; Gan, Liangzhi
With the rapid development of 3D scanners, graphic accelerated hardware and modeling tools, the application of 3D model databases is growing in both numbers and size. There is a pressing need for effective content-based 3D model retrieval methods. In this paper, a novel 3D model retrieval scheme called Fuzzy Clustering for Physical Descriptor is proposed. First, a multi-scale indexing of 3D model database is generated for fast matching by using fuzzy clustering for a concise descriptor named as partial physical descriptor, and then a novel and effectiveness descriptor named as the global physical descriptor is embedded into feature matching with the generated indexing for obtaining more accurate retrieval results. Several retrieval performance measures demonstrate that the proposed approach is superior to other methods and robust to the missing polygons and noise.